THE EFFECT OF INQUIRY TRAINING ON LEARNING MODEL USING MACROMEDIA FLASH AND CREATIVITY ON STUDENT’S SCIENCE PROCESS SKILLS - Santro Nomember Manalu; Prof. Motlan; Nurdin Siregar (Universitas Negeri Medan, 2018)
This research aimed to determine whether students on science process skills that were learned by inquiry training model using macromedia flash will be better than conventional learning, to know whether the science process skills of students who have creativity above average was better than students who have creativity below the average, to find whether there was an interaction between instructional inquiry training model used macromedia flash with creativity on students process science skill. This research was quasi experiment research with two group pretest-posttest design. The research population was the whole of the XIth grade of SMA Negeri 4 Medan, 2nd semester of 2016/2017 academic year. The sample of research were taken by cluster random class, consist of 80 students. Class XI-1 was experiment class, consists of 40 students learned by inquiry training on learning model used macromedia flash. Class XI-2 was control class, consists of 40 students taught conventional learning. The instruments consists of two types namely: essay test science process skill consists of 10 questions and essay test of creativity consists of 5 questions. The conclusion are the science process skill of student taught by inquiry training on learning model used macromedia flash was better than conventional learning, the second , the science process skills of students who have creativity above average was not better than students who have below average creativity and the third that there is no interaction between inquiry training model using macromedia flash and conventional learning with creativity in an effort to improve students' science process skills